Surgery, Anesthesia and Intensive Care Environment Induce Delirium-Like Behaviors and Impairment of Synaptic Function-Related Gene Expression in Aged Mice - Illendula, Meghana (Front Aging Neurosci, 2020)
OBJECTIVE: To establish a clinically relevant mouse model of perioperative delirium. METHODS: Aged C57BL/6J mice were tested at baseline in the Y-maze novel arm preference, buried food, simple discrimination task of the attentional set-shifting test, and open field tests. They were subsequently randomized to insult (anesthesia, surgery, and Intensive Care Unit environment) or control group. Insult-exposed mice received laparotomy under sevoflurane anesthesia, propofol sedation and exposure to intermittent lights, sounds and cage shaking. Controls did not receive anesthesia, surgery, or intensive care environment. All mice were tested in the Y-maze novel arm preference, buried food, attentional, and open field tests at the end of intensive care environment (0 h) and every 6 h up to 24 h. Mouse hippocampi were collected at 24 h for gene expression analyses. RESULTS: Surgery, anesthesia and Intensive Care environment decreased the entries in the Y-maze novel arm at 0 h (P = 0.001), 6 h (P < 0.001), 18 h (P = 0.002), and 24 h (P = 0.029). Insult exposure increased the latency to find a buried cereal reward at 18 h (P = 0.035) and 24 h (P = 0.027), and increased the trials to criterion in the reverse compound discrimination (P = 0.013) and extradimensional shift (P < 0.001) tasks of the attentional test. The overall incidence of delirium was 72% in A/S/I mice. Messenger RNA levels of synuclein alpha (−3.785 fold change relative to controls), Neurotrophic Receptor Tyrosine Kinase1 (−2.267), and syntaxin1a (−1.498) were decreased in the hippocampus of mice 24 h after insult exposure. Protein levels of syntaxin 1a (P = 0.012), Neurotrophic Receptor Tyrosine Kinase1 (P = 0.039), synuclein alpha (P = 0.017), phosphorylated synuclein alpha (P = 0.008), synaptophysin (P = 0.002), postsynaptic density protein 95 (P = 0.003), and microtubule-associated protein 2 (P = 0.013) were also decreased, relative to controls. CONCLUSION: Surgery, anesthesia and Intensive Care environment impaired mouse behaviors that depend on attention, memory, and thought organization. The changes were acute in onset and fluctuating in time. Mice with delirium exhibited decreased expression of key synaptic function-related genes. The behavioral changes induced by anesthesia, surgery, and Intensive Care environment in aged mice are consistent with the clinical features of human delirium, and support the use of this animal model for future mechanistic studies of perioperative delirium.